Criminal Response Formulation Policy Distribution News (Hoax) through Social Media - Hendral Veno; Chepi Ali Firman; Dey Ravena; Aji Mulyana (Journal La Sociale, 2021)
The spread of fake news (hoax) is increasingly prevalent nowadays. Hoax is fake news that often appears on the internet and aims to spread panic and mass fear. Many irresponsible individuals carried out an activity to achieve a goal that can cause unrest, chaos, and disrupt state security. The research objective is to understand the criminal provisions in the ITE Law into conditions that follow the development of the criminal act of spreading hoaxes—knowing the policy formulation in handling the spread of fake news (hoax) through social media in Indonesia in the future. The approach method used in this research is a normative juridical approach. The types of data used in this study are secondary data and primary data. This research is classified as a kind of qualitative research. The results of this study indicate that: The provisions that follow the development of the criminal act of spreading fake news (hoax) are seen from several aspects. First, the factory itself, the second legal factor of law enforcement officers, the third is facilities and infrastructure, fourth, the community factor. In terms of this aspect, the formulation of criminal law in dealing with fake news in the future looks better and more complete, especially in the concept of the Criminal Code, which regulates things that can be convicted regarding fake news and hate speech, the form of fake news and hate speech in cyberspace. The current criminal law policy still has shortcomings, especially in terms of policy formulation.